Strategi Pelatih Tari Bali dalam Meningkatkan Minat Belajar Siswa di Pasraman Widya Santa Dharma Lingkungan Sweta Cakranegara Kota Mataram - Miantari, Ni Made Dwi; Armayani, Ni Made Ria Taurisia; Prajawati, Yani Timor (Yayasan Alpatih Harapan Semesta, 2024)
This study explains that the strategy of Balinese dance trainers has an important role in increasing interest in learning sisya in Pasraman Widya Santa Dharma. The research method uses qualitative methods. The dance learning process at Pasraman Widya Santa Dharma is held on Monday and Thursday at 16.00-18.00. The obstacles of Balinese dance trainers in increasing their interest in learning in Pasraman Widya Santa Dharma are, first, lack of parental support; secondly, transportation; third, school activities; Fourth, different children's comprehension; fifth, interest; sixth, age; Seventh, time. The strategies of Balinese dance trainers in increasing interest in learning sisya at Pasraman Widya Santa Dharma are, first, varied Balinese Dance Training; second, involving Sisya in Dance Performance; third, the division of groups; carry out an independent dance exam.